Training in SMEs and its relationship to profitability. (4th February 2010) - O'Regan, Nicholas; Stainer, Lorice; Sims, Martin
The continuous development of employee potential is dependent on training at every level to acquire improved skills. While attention has been devoted to its contribution within organisations, there is a dearth of research on its effectiveness within the SME sector. The impact of training on performance and profitability in manufacturing SMEs is investigated. Three training groups are identified and examined in relation to the emphasis placed: employee input on decision making, influence on working practices and creativity on performance objectives. Those who utilise HR professionals seem to perform better than those who invest in training without HR input.